2000
DOI: 10.2223/jped.45
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in inflammation in patients with juvenile rheumatoid arthritis

Abstract: Objective: To determine the level of cellular oxidative stress blood markers and the enzymatic system of antioxidant defense establishing the oxidative profile in patients with Juvenile Rheumatoid Arthritis.Methods: Case-control study that included 64 patients (46 of female sex) with Juvenile Rheumatoid Arthritis (JRA) following clinical control in the Pediatric Rheumatology Service of the Vall d'Hebron Hospital, Barcelona, Spain. The patients were separated in three subtypes based on the pattern of onset with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
17
2
2
Order By: Relevance
“…Ramos et al (2000) found that OxS markers such as plasma levels of hydroperoxide and malon dialdehyde were significantly higher in patients with JRA when compared with the controls, especially in the systemic sybgroup, which is considered to be the most severe form of the disease [5]. Renke et al (2007) found an increased level of plasma protein carbonyls at diagnosis and after a year of treatment in JIA patients as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ramos et al (2000) found that OxS markers such as plasma levels of hydroperoxide and malon dialdehyde were significantly higher in patients with JRA when compared with the controls, especially in the systemic sybgroup, which is considered to be the most severe form of the disease [5]. Renke et al (2007) found an increased level of plasma protein carbonyls at diagnosis and after a year of treatment in JIA patients as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…HOCl belongs to reactive oxygen species (ROS). Cells that are present in infla med joints (macrophages, neutrophils, lymphocytes, and endothelial cells) are capable of producing ROS, which damage the articular cartilage [5]. Plasma MPO levels are accepted as a new marker for both inflammation and oxidative stress (OxS), whereas both condi tions have an impact on vascular dysfunc tiona lities [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis is a chronic relapsing immunoinflammatory multisystem disease with predominant synovial proliferation and destruction of the articular cartilage and bone (28) (21). It has been shown that, especially in RA, monocytes produce 2.7 times more oxygen radicals than controls (22).…”
Section: Discussionmentioning
confidence: 99%
“…These systems consist of nonenzymatic antioxidants-including nonprotein antioxidants with low molecular weights (vitamins A and E, beta-carotene, uric acid) and of enzymes such as SOD, catalase, glutathione peroxidase, and glutathione reductase. The activity of SOD, a catalyst for dismutation of superoxide radicals into H 2 O 2 and into molecular oxygen, protects cell and tissues from superoxide radicals and other peroxides (28). In several studies, lower activity of SOD (29) and no change in SOD (30) were shown.…”
Section: Discussionmentioning
confidence: 99%